Gene and Mirna Regulatory Networks During Different Stages of Crohn's Disease. (18th January 2019) - Verstockt, Sare; De Hertogh, Gert; Van der Goten, Jan; Verstockt, Bram; Vancamelbeke, Maaike; Machiels, Kathleen; Van Lommel, Leentje; Schuit, Frans; Van Assche, Gert; Rutgeerts, Paul; Ferrante, Marc; Vermeire, Séverine; et al.
Abstract: Background and Aims: Early treatment of Crohn's disease [CD] is required in order to optimize patient outcomes. To this end, we need to gain a better understanding of the molecular changes at the onset of CD. Methods: As a model for the earliest mucosal CD lesions, we study post-operative recurrent CD [Rutgeerts score ≥ i2b]. We are the first to analyse gene and microRNA [miRNA] expression profiles in ileal biopsies from these patients, and compare them with those of newly diagnosed [≤18 months] and late-stage [>10 years after diagnosis] CD patients. Results: Except for one gene [ WNT5A ], there are no differential genes in CD patients without post-operative recurrence [i0], showing that previous disease did not influence gene expression in the neoterminal ileum, and that this model can be used to study early mucosal CD lesions. Gene expression and co-expression network dysregulation is more pronounced in newly diagnosed and late-stage CD than in post-operative recurrent CD, with most important modules associated with [a]granulocyte adhesion/diapedesis, and cholesterol biosynthesis. In contrast, we found a role for snoRNAs/miRNAs in recurrent CD, highlighting the potential importance of regulatory RNAs in early disease stages. Immunohistochemistry confirmed the expression of key dysregulated genes in damaged/regenerating epithelium and immune cells in recurrent CD. Conclusions: Aside from regulatory RNAs, there are no clear gene signatures separating post-operative recurrent, newly diagnosed, and late-stage CD. The relative contribution of dysregulated genes and networks differs, and suggests that surgery may reset the disease at the mucosal site, and therefore post-operative recurrent CD might be a good model a good model to study to study early mucosal CD lesions.